2021
DOI: 10.1002/vetr.515
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the attitudes of Bavarian farmers towards pain in cattle and how they differ from the attitudes of bovine veterinarians

Abstract: Background: Assessment of pain in cattle depends on the observer's experience and evaluation. Only a few studies compare veterinarians' and farmers' attitudes towards pain in cattle. Methods: A questionnaire was sent to 1097 cattle practitioners and 3750 farmers. Return rate was 26.2% for veterinarians and 15.4% for farmers, respectively. Respondents were asked to score the painfulness of procedures and diseases in cattle on a numerical rating scale from 0 (no pain) to 10 (worst pain imaginable), to give their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In a survey study of Canadian veterinarians, Hewson et al, (18) expressed the provision of analgesia as a percentage of calves receiving analgesia and showed that 6.9% and 18.7% of beef and dairy calves six months of age or less received analgesia and 19.9% and 33.2% of beef and dairy calves greater than six months of age received analgesia for castration. Tshoner et al, (89) of both local and systemic analgesia by veterinarians as compared with producers for surgical castration in calves but also reported that surgical castration was rated as one of the most painful procedures out of the those included in the survey; although it is challenging to compare across studies due to differences in methodology, in the current study, the pain associated with surgical castration was not rated as high. Despite substantial evidence that surgical castration causes pain in cattle (e.g., 11-13, 54, 57, 61-63) and some regulatory guidance existing in countries outside of the United States, the provision of pain mitigation for surgical castration, although increasing has not reached full adoption as a consistently implemented best management practice.…”
Section: Discussionmentioning
confidence: 54%
“…In a survey study of Canadian veterinarians, Hewson et al, (18) expressed the provision of analgesia as a percentage of calves receiving analgesia and showed that 6.9% and 18.7% of beef and dairy calves six months of age or less received analgesia and 19.9% and 33.2% of beef and dairy calves greater than six months of age received analgesia for castration. Tshoner et al, (89) of both local and systemic analgesia by veterinarians as compared with producers for surgical castration in calves but also reported that surgical castration was rated as one of the most painful procedures out of the those included in the survey; although it is challenging to compare across studies due to differences in methodology, in the current study, the pain associated with surgical castration was not rated as high. Despite substantial evidence that surgical castration causes pain in cattle (e.g., 11-13, 54, 57, 61-63) and some regulatory guidance existing in countries outside of the United States, the provision of pain mitigation for surgical castration, although increasing has not reached full adoption as a consistently implemented best management practice.…”
Section: Discussionmentioning
confidence: 54%
“…There is also limited comparative work between the attitudes to pain between both veterinarians and farmers. Tschoner et al ( 12 ) reported that there was no significant differences between pain scores of Bavarian veterinarians and farmers. In contrast, Thomsen et al ( 13 ) reported that Danish dairy farmers gave higher pain scores compared to veterinarians.…”
Section: Introductionmentioning
confidence: 99%
“…In surveys of veterinarians' attitudes, women assigned higher pain levels than men for different surgical procedures in dogs and cats [52][53][54] . For large animals, women farms and veterinarians had different perceptions of pain in bovines [55][56][57][58] , equines 59,60 , and swine 61 due to painful procedures and diseases in comparison with men. Additionally, women have scored higher pain than men when using a visual analogue scale assessing adults and children painful human patients [47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…More speci cally, in questionnaires about small animal veterinary attitudes, women assigned higher pain levels for different surgical procedures than men [52][53][54] . Additionally, women farms and veterinarians had different perceptions of pain than men when asked about painful procedures and diseases in bovines [55][56][57][58] , equines 59,60 , and swine 61 . Speci cally for the pain-altered behavior scales, the observers' gender impacted grimace scales for macaques 13 , sows 28 , and donkeys 23 , as well as wholebody behavioral pain scales in cats 34,62 and dogs 62 .…”
Section: Introductionmentioning
confidence: 99%